Algunos desafíos y oportunidades de las revistas especializadas en humanidades en Latinoamérica: redes y trampas - Far´ías, Miguel (Colombian Applied Linguistics Journal, 2018)
Motivated by the creation of Árboles y Rizomas, an academic journal in linguistic and literary studies, as well as by the 20th anniversary of the Colombian Applied Linguistics Journal, this paper examines both the challenges and opportunities that journals in the humanities face in Latin America. From a critical and qualitative perspective, two challenges are identified—that of validating the humanities amidst productivity indexing, and of reflecting upon the hegemonic directionality of the flow of scholarship in the North-South dichotomy. The opportunities deal with establishing networks of collaboration among academic journals as well as with the optimization of the processes of publication.